Cultural humility strategies for recruitment and retention of minoritised participants: a scoping review protocol - Mireille Chehade; Kellie McLean; Samar Mohsen Ashmawi; Moroni Fernandez Cajavilca; Baomi T Phung; Maya N Clark-Cutaia; Brynne Campbell Rice (BMJ Open, 2025)
Introduction Cultural humility practices are shown to be effective when working with diverse populations in healthcare settings. Research recruitment and retention among minoritised groups are essential to address health inequities. Given the successful application to healthcare settings, cultural humility practices may hold promise for recruiting and retaining minoritised individuals. However, little is known about how these practices may be applied to health research. The objective of this scoping review is to understand the extent to which cultural humility practices are applied to health research and how they may be leveraged to optimise recruitment and retention among minoritised populations.Methods and analysis This scoping review will follow the Joanna Briggs Institute methodology for scoping reviews. Databases to be searched will include Medline (Ovid), CINAHL (EBSCOhost), EMBASE (Ovid), PsycINFO (Ovid) and Web of Science Core Collection. Literature from 1993 to 2024 that captures the concept of cultural humility in health research with racial and ethnic or gender and sexual minoritised populations in the USA will be considered. The identified pool of records will be imported to Covidence, an online data management software. At the first screening stage, two independent reviewers will screen for title and abstract relevance. A third reviewer will be recruited to resolve discrepancies, if any. Records achieving consensus will have their full texts screened against the eligibility criteria and included in the final pool. Two tables will be developed to guide the data extraction process. The tabular format will be piloted and agreed on by all research team members. Descriptive content analysis will outline the operationalisation of cultural humility and identify strategies found effective in improving the representation of minoritised populations.Ethics and dissemination Ethical approval is not required in line with the scoping review methodology. Dissemination of the findings mapping the cultural humility strategies found effective in health research will be conducted through a peer-reviewed publication.Trial registration number Open Science Framework https://osf.io/vra7h.